Pengaruh Pengembangan Objek Wisata Kampung Gadungan Terhadap Tingkat Kunjungan Wisatawan Di Ngargoyoso Kabupaten Karanganyar - Ainun Farahin Jamsari; Titik Akiriningsih; Sunyoto Sunyoto (Sekolah Tinggi Pariwisata Sahid Surakarta, 2019)
This thesis examines the influence of the development of 4A attractions, amenities, accessibility and activities in Kampung Gadungan Ngargoyoso karanganyar Regency. This study aims to address questionable issues regarding the development of Kampung Gadungan and the effect of development on the level of tourist visits. Writing of this Thesis is presented in a descriptive qualitative way to get an overview of information related to development, especially in 4A attractions, amenities, accessibility, Activities. The method used to collect data is the study of documents, interviews, observations. The data obtained were then analyzed qualitatively by being presented descriptively. The results showed that the development in attractions, amenities, accessibility and activities had been carried out by the manager of Kampung Gadungan quite well and this had an effect on increasing tourist visits.